Nurturing Salafi manhaj; A study of Salafi pesantrens in contemporary Indonesia - Wahid, Din (UI Scholars Hub, 2014)
This study is about the role of Salafi pesantrens (Islamic boarding schools) in Salafi da'wa (conveying or inviting to the way of Islam) in Indonesia. A Salafi pesantren is a pesantren that teaches Salafism which mostly derives from the works of Muhammad ibn 'Abd al-Wahhab, the founder of Wahhabism in Saudi Arabia. Salafi pesantrens started to emerge in the late 1980s and were established by graduates from Saudi Arabia and Yemen universities, and supported by alumni of the Institute for the Study of Islam and Arabic (LIPIA) in Jakarta. While the precise number of Salafi pesantrens is unavailable, it is estimated that the number reaches 50 pesantrens. Salafi pesantrens not only teach their students about Salafism, but also accustom them to practice the Salafi manhaj (path) in their daily life. The study focuses on three pesantrens: al-Nur al-Atsari in Ciamis, Assunah in Cirebon (both in West Java), and al-Furqan in Gresik, East Java. I analyse various aspects of these educational institutions: their historical development, community responses, educational programs, curriculum, methods of instruction, students' lives and activities, networks and fundraising.